The Information Content of Annual Earnings Announcements A Trading Volume Approach - Berhanu Beza; Ainun Na'im (The Indonesian Journal of Accounting Research, 2013)
The overall purpose of the study is to investigate the information content of annual earnings announcements in terms of trading volume activities in Jakarta Stock Exchange market of the year 1995. To achieve this objective, 30 firms meeting the following criteria have taken: (1) companies having stocks active for the periode under consideration, (2) having a continuous listing in the exchange for the study period, (3) companies issuing audited financial statement for the year 1994, (4) companies having no news announcement except release of annual earnings announcements.This study uses secondary data the measurement of which is made on an ordinal scale. The statistical techniques used in making the data analysis are the Wilcoxon signed ranks test and the Spearman’s rank correlation coefficients. Based on the data analysis for this study, researcher noticed that security trading volume significantly increases when companies announce annual earnings to the time before the announcement.Morever, findings show that there is a correlation between the unexpected trading volume and the absolute value of the magnitude unexpected earnings. Finally, it also show that there is weither a correlation between unexpected trading value with the size of the firm, mor is there a correlation between the size of the firm and unexpected earnings. Keyword: Unexpected Trading Volume; Unexpected Earnings; Firm size.